Violência midiática: a necessidade de seu reconhecimento para a efetivação dos direitos humanos das mulheres - Faleiros, Juliana Leme (2016)
Abstract Violence against women comes up in different ways along history being only at the end of 20th century the equality of their rights to the human rights. Although despite the legal progress in national and international agencies, the reality to them is still hostile. In Brazil, for example, we are able to see that in a ranking of 84 countries, the country is the 7th linked to murder of women, which is the highest point of the violence cycle and it is added to other ways of subjugation expressed in the day by day routine. It's necessary to understand which are the social structures that cooperate to the continuity of this scenario to be able to face this problem and, according to the media importance in the Brazilian society, the present research intends to look critically to the relation between media and women's issues, analyzing if its influence contributes or not for the reproduction of these social oppressive ways. The objective is to investigate the role that communication means are developing in the debate related to gender and, for that, it is used research data produced by official institutions as well as NGO, about the women's vulnerability together with symbolic violence of Pierre Bourdieu in his literary work, “A dominação masculine” – “Male domination”. Based on this concept we input in this research his idea of male dominance being reproduced in social relations and, based on understanding that means of communication deal with such relations, the inequality of gender still goes on, being the dominated mediatic violence. The defense of the inclusion of such comprehension of oppression against women in the Brazilian internal protective law, is one of the considerations presented at the end of this study , having as reference Argentina and Venezuela because after a broad list of different violence ways, we'll be able to visualize the production of stereotypes in the means of communication and it'll become possible its social combat.